Media Effect About Corruption News To The Community Trust on Village Performance - Ike Wanusmawatie; Mahandhika Hendy Firmanda; Rendra Eko Wismanu (Indonesian Association for Public Administration (IAPA), 2020)
The aim of this study is to analyze the effect of media coverage on the Village Fund corruption to the community's trust regarding with village performance, especially village government. Village is sub system of local government. This research uses quantitative with explanatory method. The collecting the data uses questionnaires while, samples were 60 people. Sampling using stratified random. The study uses inferential statistical tests. Hypothesis testing is done by the coefficient of determination test; f test; and t test. Based on the results of the data obtained, it was found that there was an influence of reporting on the corruption of the Village Fund to the community trust on village government performance. The coefficient of determination test shows that the three variables of the media agenda, public agenda, and policy agenda affect the variable of village community trust by 52.7%. It can be concluded that media coverage has an effect on public trust. Thus, it is strengthening the concept of the penta helix in governance. It is show at the future, the role of media taken into account in governance process.